CHARACTERISTICS OF EFFICIENT USE OF ECONOMIC AND ECOLOGICAL MECHANISMS IN THE REGION (Marketing Journal, 2025)
This article discusses the features of the use of economic and ecological mechanisms in the region. It also presents conclusions and proposals for the effective use of economic and ecological mechanisms in the region.
Keywords: Region; mechanism; economic and ecological mechanism; problem; sustainability